Heuristic evaluation of stock exchange mobile application in Malaysia - Hussain, Azham; Barakat, Mustafa M.; Zaaba, Zarul Fitri (Science and Engineering Research Support Society, 2020)
In recent years, heuristic evaluation has focused to improving the efficiency and effectiveness of applications. This technique is considered as the most effective tool that is used in human-computer interaction studies to test the usability of information systems. Moreover, this technique is widely adopted to analyze the usability of applications as it is inexpensive and quick.The objective of this study is to use the heuristic evaluation principals to assess the effectiveness of the stock exchange mobile application in Malaysia. Questionnaire survey method was used and data were collected by 25 participants from Kuala Lumpur Stock Exchange (KLSE). The heuristic evaluation was conducted by 25 experts to examine the usefulness of stock exchange mobile application. The results revealed that stock exchange application is an effective and useful application that has all required features. Meanwhile, findings also postulated that most of the users show agreeableness regarding the applications of principals of heuristics evaluation in this application. These heuristic principals can further used to avoid the usability gaps in this stock exchange application.This study also gives guidelines to designers for taking corrective measures during the designing of the applications for the stock exchange. Additionally, these guidelines help to provide solutions in the future that how designers may improve the user interface of these stock exchange applications that may improve the experience of users.